Bible For Kids: Aplikasi Pendamping Orang Tua Mewujudkan Pendampingan pada Pendidikan Agama Kristen Anak di Keluarga - Purba, Sudiarjo (Sekolah Tinggi Teologi Nusantara, 2024)
The background for writing this article is the widespread use of smartphones among children and the many applications available on Android with religious affiliations, including Christianity, that not many parents know about. The purpose of this research is to convey to parents that the responsibility to realize Christian Religion Education (CRE) for children in the family can be helped by the availability of the Bible for Kids application. The scope of the research is an exploration of the Android application, namely Bible for Kids, which is linked to CRE Children in the family. The findings and conclusions of this research are that the Bible for Kids application is very suitable for parents to use as a companion application in realizing PAK for children in the family, especially in increasing children's Bible knowledge through stories, coloring activities, games and other activities available on the application the.Abstrak:Latar belakang penulisan artikel ini adalah maraknya penggunaan smartphone pada anak dan banyaknya aplikasi yang tersedia di android berafiliasi keagamaan termasuk keagamaan Kristen yang belum banyak orang tua ketahui. Tujuan penelitian ini adalah untuk menyampaikan kepada orang tua bahwa tanggung jawab mewujudkan PAK Anak di keluarga dapat terbantu dengan tersedianya aplikasi Bible for Kids. Ruang lingkup penelitian adalah eksplorasi terhadap aplikasi android yaitu Bible for Kids, yang dikaitkan dengan PAK Anak di keluarga. Hasil temuan dan kesimpulan pada penelitian ini adalah bahwa aplikasi Bible for Kids sangat cocok untuk dimanfaatkan oleh orang tua sebagai aplikasi pendamping dalam mewujudkan PAK Anak di keluarga khususnya dalam meningkatkan pengetahuan Alkitab anak melalui cerita, aktivitas mewarnai, game, dan aktivitas lainnya yang tersedia pada aplikasi tersebut.